Is First Rib Fracture a Culprit or a Sign of Injury Severity? It Is Both. Issue 8 (August 2018) - Fokin, Alexander; Wycech, Joanna; Picard, Eric; Weisz, Russell; Puente, Ivan
Abstract : Objectives: First rib fractures (first RFX) have been correlated with increased morbidity and mortality. Whether this is due to the fracture of the rib itself or due to an increased number of associated injuries remains debatable. Design: Retrospective cohort study. Setting: Level 1 trauma center. Patients: One thousand eighty-nine patients with rib fractures divided into 3 groups: group A (n = 44) with isolated first RFX, group B (n = 116) with first RFX combined with other rib fractures, and group C (n = 929) with rib fractures without first RFX. Intervention: None. Outcome measurements: Age, sex, Injury Severity Score, mortality, number of ribs fractured (RFX), incidences of flail chest, multiple coinjuries, hospital and intensive care unit lengths of stay, and duration of mechanical ventilation. Results: Group A, when compared with group B, had significantly lower Injury Severity Score, RFX, rates of flail chest, pulmonary coinjuries, and shorter hospital length of stay and intensive care unit length of stay. Group A compared with group C had significantly lower age, RFX, rates of flail chest, and hemopneumothorax. In group B, all outcome measurements were significantly higher than those in group C. Incidence of subclavian artery, brachial plexus, and first thoracic vertebra injuries was significantly higher in group A. Frequency of traumatic brain and orthopaedic coinjuries was comparable in both groups with first RFX. Conclusions: Isolated first RFX alone are associated with higher incidence of injuries to subclavian structures and the first thoracic vertebrae. When they are combined with fractures of other ribs, the overall severity of trauma expands significantly. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.